Metal composite oxide cordierite monolithic catalyst for removing short-chain hydrocarbons as well as preparation method and application of metal composite oxide cordierite monolithic catalyst

The metal composite oxide cordierite monolithic catalyst prepared by ball mill coating method solves the problem of low-temperature removal efficiency of short-chain hydrocarbons in the prior art, and achieves an efficient synchronous removal effect below 550°C.

CN119406420APending Publication Date: 2025-02-11SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411462147.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing cordierite honeycomb ceramic support catalysts have challenges in the low-temperature applications of short-chain hydrocarbons, and it is difficult to effectively remove short-chain hydrocarbons in waste gas.

Method used

The metal composite oxide cordierite monolithic catalyst was prepared by ball mill coating method, and a stable precursor solution was formed by sonication and magnetic stirring. Then, aqueous ammonia solution was added to form a precipitate. After washing, drying, calcining and ball milling, the final step is to A catalyst layer is formed by coating the honeycomb ceramic support.

Benefits of technology

The catalyst exhibits excellent synchronous removal activity of short-chain hydrocarbon VOCs below 550°C and maintains stable activity for a long time, significantly improving the low-temperature removal efficiency of short-chain hydrocarbons in exhaust gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119406420A_ABST
    Figure CN119406420A_ABST
Patent Text Reader

Abstract

The invention discloses a metal composite oxide cordierite monolithic catalyst for removing short-chain hydrocarbons as well as a preparation method and application of the metal composite oxide cordierite monolithic catalyst. The method comprises the following steps: putting an active metal source precursor into deionized water, performing ultrasonic dispersion, and stirring until the active metal source precursor is completely dissolved to form a stable precursor solution; dropwise adding an ammonia water solution into the precursor solution in the stirring process until precipitate appears; and washing with deionized water, drying and calcining to obtain the transition metal composite oxide. The preparation method comprises the following steps: adding a transition metal composite oxide and a binder into deionized water, stirring, and grinding into slurry; adding noble metal into the slurry, and uniformly stirring to obtain coating slurry; the honeycomb ceramic cordierite carrier is subjected to soaking pretreatment in acid, drying and calcining. And soaking the honeycomb ceramic cordierite carrier in the coating slurry, taking out the honeycomb ceramic cordierite carrier, purging, drying, and calcining to obtain the catalyst. The catalyst prepared by the method shows excellent multi-component short-chain hydrocarbon catalytic oxidation activity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of honeycomb ceramic carrier catalyst preparation, and in particular relates to a metal composite oxide cordierite monolithic catalyst suitable for catalytic combustion of short-chain hydrocarbons and a preparation method thereof. Background Art

[0002] Volatile organic compounds (VOCs) refer to organic compounds with a boiling point of 50 to 260°C at an atmospheric pressure of 101.3 kPa, mainly including non-methane hydrocarbons, oxygen-containing non-methane hydrocarbons, nitrogen-containing organic compounds, halogenated hydrocarbons and sulfur-containing organic compounds. Studies have shown that long-term exposure to VOCs pollution can cause leukemia, nervous system depression, respiratory diseases, cancer and other diseases, which are harmful to health. Among volatile organic compounds, straight-chain short-chain alkanes (C n H 2n+2 , n ≥ 2) have received considerable attention. Generally, they are difficult to decompose due to their high thermodynamic stability. Ethane and propane are representative non-methane volatile organic compounds (NMVOCs), and both have become the focus of regulatory scrutiny due to strict flue gas emission standards. Therefore, various technologies have been developed to reduce their emissions. Catalytic oxidation technology has been proven to be an effective method for eliminating alkanes and their derivatives. However, due to the inherent strong CH bonds, the development of high-performance catalysts, especially those for low-temperature applications, still has certain difficulties. Cordierite honeycomb ceramic carrier catalyst is currently a more commonly used catalyst type for VOCs purification in industry, but its low-temperature application in short-chain alkanes is challenging. Summary of the invention

[0003] The present invention provides a metal composite oxide cordierite monolithic catalyst for removing short-chain hydrocarbons in exhaust gas, which is prepared by a ball milling coating method. The catalyst exhibits excellent short-chain hydrocarbon VOCs simultaneous removal activity below 550°C and can maintain stable activity for a long time. The catalyst has good application prospects in the low-temperature removal of short-chain hydrocarbon VOCs in exhaust gas.

[0004] The technical solution of the present invention is as follows.

[0005] A method for preparing a metal composite oxide cordierite monolithic catalyst for removing short-chain hydrocarbons is prepared by ball milling and coating method, and the specific steps include:

[0006] (1) placing an active metal source precursor in deionized water, ultrasonically treating it, transferring it to a magnetic stirrer, and stirring it continuously until it is completely dissolved to form a stable precursor solution; the active metal comprises at least one element selected from the group consisting of Mn, Fe, Ni, Co, Ce, Zn, and Cu;

[0007] (2) adding an aqueous ammonia solution dropwise to the precursor solution while stirring until precipitation occurs; washing the obtained precipitate with deionized water, drying, rolling and screening, and finally calcining to obtain a transition metal composite oxide;

[0008] (3) preparing a sol according to a binder and deionized water mass ratio of 1: (0-100), dispersing the transition metal composite oxide into the sol according to a solid sol mass ratio of 0.05-0.4, stirring evenly and grinding into a slurry using a ball mill;

[0009] (4) adding precious metal Pt or Pd to the slurry and stirring to obtain a coating slurry, wherein the amount of Pt or Pd added is 0 to 1.5 wt % of the transition metal composite oxide;

[0010] (5) pre-treating the honeycomb ceramic cordierite support by immersing it in an acid, drying it, and calcining it;

[0011] (6) The pretreated honeycomb ceramic cordierite carrier is immersed in the coating slurry, taken out, purged, dried, and calcined to obtain a monolithic catalyst coated with a complete catalyst layer.

[0012] A further preferred technical solution is: in step (1), the active metal source is nickel nitrate, cobalt nitrate, cerium nitrate, manganese nitrate, zinc nitrate, and iron nitrate. The preferred metal source contains nickel, manganese, and cobalt, and the molar ratio thereof is 1:4:20; the preferred metal source is iron and cerium, and the molar ratio thereof is 1:(1-4); the preferred metal source is iron and cobalt, and the molar ratio thereof is 1:(1-4). In step (4), the noble metal source is platinum nitrate, palladium nitrate, and chloroplatinic acid, and the preferred loading amount is 0-1.5wt% of the transition metal composite oxide. Under this condition, the catalyst has the highest catalytic oxidation activity of short-chain hydrocarbons.

[0013] A further preferred technical solution is: in step (2), the mass concentration of the ammonia solution is 25-28 wt %.

[0014] A further preferred technical solution is: in step (2), step (5) and step (6), the drying temperature is 70 to 80° C. and the drying time is 10 to 12 hours.

[0015] A further preferred technical solution is: in step (2), step (5) and step (6), the calcination temperature is 400-600° C. and the calcination time is 3-5 hours.

[0016] A further preferred technical solution is: in step (3), the binder is one of pseudo-boehmite, aluminum sol, silica sol and hydroxymethyl cellulose, and the mass ratio of the binder to water in the prepared sol is 1: (0-100).

[0017] A further preferred technical solution is: in step (3), the mass ratio of the catalyst to the sol solid sol is 0.05 to 0.4. The ball milling slurry time is 3 to 6 hours.

[0018] A further preferred technical solution is: in step (5), the acid used in the acid pretreatment is one of oxalic acid, nitric acid and hydrochloric acid, the mass fraction of the pretreatment acid is 5-10wt%; and the acid pretreatment time is 8-12h.

[0019] A further preferred technical solution is: in step (6), the honeycomb ceramic cordierite is immersed in the slurry for 10 to 30 minutes.

[0020] The invention discloses an application of a metal composite oxide cordierite monolithic catalyst in removing short-chain hydrocarbons in exhaust gas, wherein the multi-component short-chain hydrocarbon removal temperature is 140-550°C.

[0021] The present invention also provides the application of the catalyst to the simultaneous removal of short-chain hydrocarbons in exhaust gas within a medium and low temperature range. The catalyst exhibits the performance of simultaneous removal of ethane and propane under the condition that the temperature window is below 550°C.

[0022] The present invention further provides that the catalyst can maintain stable catalytic oxidation activity in an exhaust gas environment with high concentration of short-chain hydrocarbons.

[0023] Compared with the prior art, the main advantages of the present invention include:

[0024] The catalyst prepared by ball milling coating in the present invention has a simple preparation method and low cost, and has excellent short-chain hydrocarbon simultaneous removal efficiency (>90%) under conditions above 420° C., making it have application prospects in the field of multi-component short-chain hydrocarbon simultaneous removal. DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with the accompanying drawings and specific examples. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0026] Example 1

[0027] (1) According to the molar ratio of n(Ni):n(Mn):n(Co)=1:4:20 in the final sample, 34.9236g of Co(NO3)2·6H2O powder, 1.7447g of Ni(NO3)2·6H2O powder and 2.789mL of 50wt% Mn(NO3)2 solution were weighed and added into 150mL of deionized water, dispersed by ultrasound and stirred for 5min until fully dissolved to form a precursor solution, and a 25wt% ammonia solution was slowly added into the precursor solution and stirred continuously for 1h until a precipitate appeared. The obtained precipitate was repeatedly washed 3 to 5 times with deionized water by centrifugation, washed 1 to 2 times with ethanol, then dried at 80°C for 12h, and finally calcined at 600°C for 3h to obtain the transition metal composite oxide.

[0028] (2) 5 g of nickel-manganese-cobalt transition metal composite oxide was mixed with 50 g of 30 wt% aluminum dihydrogen phosphate sol at a solid sol mass ratio of 0.1, stirred evenly, and then transferred to a ball mill for 4 hours to obtain a coating slurry.

[0029] (3) First, the honeycomb ceramic cordierite carrier was soaked in a 10wt% oxalic acid solution for 12h, dried at 80°C, and then calcined at 600°C for 3h. The pretreated honeycomb ceramic cordierite carrier was soaked in the prepared slurry for 10min, taken out and purged evenly, dried at 80°C for 12h, and then calcined at 600°C for 3h to obtain a finished product.

[0030] (4) Test process: A catalyst sample with a height of 2.5 cm and a diameter of 1.4 cm was cut from the obtained cordierite monolithic catalyst, and the catalyst sample was placed in a fixed-bed steel tube reactor. The synergistic catalytic oxidation performance of ethane and propane at 75 to 550° C. was tested in a simulated atmosphere (ethane: 1000 ppm, propane: 2000 ppm, O2: 3 vol%, and the rest N2). The total gas flow rate was 200 mL / min (volume space velocity = 10000 h -1 ).

[0031] Example 2

[0032] (1) According to the molar ratio of n(Fe):n(Ce)=1:1 in the final sample, 30.3g of Fe(NO3)3·9H2O powder and 32.5665g of Ce(NO3)3·6H2O powder were weighed and added to 150mL of deionized water, and then dispersed by ultrasound and stirred for 5min until fully dissolved to form a precursor solution, and a 25wt% ammonia solution was slowly added to the precursor solution and stirred for 1h until a precipitate appeared. The obtained precipitate was repeatedly washed 3 to 5 times with deionized water by centrifugation, washed 1 to 2 times with ethanol, and then dried at 80°C for 12h, and finally calcined at 600°C for 3h to obtain the transition metal composite oxide.

[0033] (2) Disperse 5 g of pseudo-boehmite in 45 g of deionized water at a mass ratio of 1:9, add 1 mL of 65-68 wt% HNO3 solution, and stir to prepare aluminum nitrate sol. Mix 5 g of iron-cerium transition metal composite oxide and 50 g of aluminum nitrate sol at a solid sol mass ratio of 0.1, stir to prepare, and then transfer to a ball mill and mill for 4 hours to obtain a coating slurry.

[0034] (3) Adding platinum nitrate in an amount of 1 wt % of platinum based on the transition metal composite oxide to the prepared slurry, stirring the mixture evenly to obtain a final coating slurry.

[0035] (4) First, the honeycomb ceramic cordierite carrier was soaked in a 5wt% nitric acid solution for 12 hours, dried at 80°C, and then calcined at 550°C for 3 hours. The pretreated honeycomb ceramic cordierite carrier was soaked in the prepared slurry for 10 minutes, taken out and purged evenly, dried at 80°C for 12 hours, and then calcined at 550°C for 3 hours to obtain a finished product.

[0036] (5) Test process: A catalyst sample with a height of 2.5 cm and a diameter of 1.4 cm was cut from the obtained cordierite monolithic catalyst, and the catalyst sample was placed in a fixed-bed steel tube reactor. The synergistic catalytic oxidation performance of ethane and propane at 75 to 550° C. was tested in a simulated atmosphere (ethane: 1000 ppm, propane: 2000 ppm, O2: 3 vol%, and the rest N2). The total gas flow rate was 200 mL / min (volume space velocity = 10000 h -1 ).

[0037] Example 3

[0038] (1) According to the molar ratio of n(Fe):n(Zn):n(Ni):n(Mn):n(Co)=1:1:1:1:1 in the final sample, 8.7309 g of Co(NO3)2·6H2O powder, 8.7237 g of Ni(NO3)2·6H2O powder, 12.12 g of Fe(NO3)3·9H2O powder, 8.9247 g of Zn(NO3)2·6H2O powder and 3.486 mL of 50 wt% Mn(NO3)2 solution were weighed and added into 150 mL of deionized water. After being dispersed by ultrasound, the mixture was stirred for 5 min until fully dissolved to form a precursor solution. A 25 wt% ammonia solution was slowly added into the precursor solution and stirred for 1 h until a precipitate appeared. The obtained precipitate is repeatedly washed 3 to 5 times with deionized water by centrifugation, washed 1 to 2 times with ethanol, then dried at 80° C. for 12 hours, and finally calcined at 600° C. for 3 hours to obtain the transition metal composite oxide.

[0039] (2) 5 g of iron-zinc-nickel-manganese-cobalt transition metal composite oxide was mixed with 50 g of 30 wt % alkaline silica sol at a solid sol mass ratio of 0.1, stirred evenly, and then transferred to a ball mill and milled for 4 h to obtain a coating slurry.

[0040] (3) First, the honeycomb ceramic cordierite carrier was soaked in 10wt% oxalic acid for 12h, dried at 80°C, and then calcined at 600°C for 3h. The pretreated honeycomb ceramic cordierite carrier was soaked in the prepared slurry for 10min, taken out and purged evenly, dried at 80°C for 12h, and then calcined at 600°C for 3h to obtain the finished product.

[0041] (4) Test process: A catalyst sample with a height of 2.5 cm and a diameter of 1.4 cm was cut from the obtained cordierite monolithic catalyst, and the catalyst sample was placed in a fixed-bed steel tube reactor. The synergistic catalytic oxidation performance of ethane and propane at 75 to 550° C. was tested in a simulated atmosphere (ethane: 1000 ppm, propane: 2000 ppm, O2: 3 vol%, and the rest N2). The total gas flow rate was 200 mL / min (volume space velocity = 10000 h -1 ).

[0042] Example 4

[0043] (1) According to the molar ratio of n(Fe):n(Co)=1:4 in the final sample, 12.12g of Fe(NO3)3·9H2O powder and 34.9236g of Co(NO3)2·6H2O powder were weighed and added to 150mL of deionized water, and then dispersed by ultrasound and stirred for 5min until fully dissolved to form a precursor solution, and a 25wt% ammonia solution was slowly added to the precursor solution and stirred for 1h until a precipitate appeared. The obtained precipitate was repeatedly washed 3 to 5 times with deionized water by centrifugation, washed 1 to 2 times with ethanol, and then dried at 80°C for 12h, and finally calcined at 600°C for 3h to obtain the transition metal composite oxide.

[0044] (2) 6.25 g of pseudo-boehmite was dispersed in 43.75 g of deionized water at a mass ratio of 1:7, and 1 mL of 65-68 wt% HNO3 was added and stirred to prepare aluminum nitrate sol. 5 g of iron-cobalt transition metal composite oxide and 50 g of aluminum nitrate sol were mixed at a solid sol mass ratio of 0.1, stirred to obtain a coating slurry after being transferred to a ball mill and milled for 4 h.

[0045] (3) Add chloroplatinic acid in an amount of 1 wt % of platinum content based on the transition metal composite oxide to the prepared slurry, and stir evenly to obtain a final coating slurry.

[0046] (4) First, the honeycomb ceramic cordierite carrier was soaked in a 10wt% hydrochloric acid solution for 12 hours, dried at 80°C, and then calcined at 550°C for 3 hours. The pretreated honeycomb ceramic cordierite carrier was soaked in the prepared slurry for 15 minutes, taken out and purged evenly, dried at 80°C for 12 hours, and then calcined at 550°C for 3 hours to obtain a finished product.

[0047] (5) Test process: A catalyst sample with a height of 2.5 cm and a diameter of 1.4 cm was cut from the obtained cordierite monolithic catalyst, and the catalyst sample was placed in a fixed-bed steel tube reactor. The synergistic catalytic oxidation performance of ethane and propane at 75 to 550° C. was tested in a simulated atmosphere (ethane: 1000 ppm, propane: 2000 ppm, O2: 3 vol%, and the rest N2). The total gas flow rate was 200 mL / min (volume space velocity = 10000 h -1 ).

[0048] Example 5

[0049] (1) According to the molar ratio of n(Fe):n(Ce)=1:4 in the final sample, 12.12g of Fe(NO3)3·9H2O powder and 52.1064g of Ce(NO3)3·6H2O powder were weighed and added to 150mL of deionized water, and then dispersed by ultrasound and stirred for 5min until fully dissolved to form a precursor solution, and a 25wt% ammonia solution was slowly added to the precursor solution and stirred for 1h until a precipitate appeared. The obtained precipitate was repeatedly washed with deionized water by centrifugation for 3 to 5 times, washed with ethanol for 1 to 2 times, and then dried at 80°C for 12h, and finally calcined at 600°C for 3h to obtain the transition metal composite oxide.

[0050] (2) 0.5 g of methyl cellulose was dispersed in 50 g of deionized water at a mass ratio of 1:100, and the mixture was stirred to obtain a hydroxymethyl cellulose sol. 5 g of iron-cerium transition metal composite oxide and 50 g of hydroxymethyl cellulose sol were mixed at a solid-sol mass ratio of 0.1, stirred to obtain a coating slurry after being transferred to a ball mill and milled for 4 h.

[0051] (3) Adding palladium nitrate in an amount of 1 wt % of the palladium content of the transition metal composite oxide to the prepared slurry, stirring evenly to obtain a final coating slurry.

[0052] (4) First, the honeycomb ceramic cordierite carrier was soaked in 5wt% oxalic acid for 12h, dried at 80°C, and then calcined at 550°C for 3h. The pretreated honeycomb ceramic cordierite carrier was soaked in the prepared slurry for 15min, taken out and purged evenly, dried at 80°C for 12h, and then calcined at 550°C for 3h to obtain a finished product.

[0053] (5) Test process: A catalyst sample with a height of 2.5 cm and a diameter of 1.4 cm was cut from the obtained cordierite monolithic catalyst, and the catalyst sample was placed in a fixed-bed steel tube reactor. The synergistic catalytic oxidation performance of ethane and propane at 75 to 550° C. was tested in a simulated atmosphere (ethane: 1000 ppm, propane: 2000 ppm, O2: 3 vol%, and the rest N2). The total gas flow rate was 200 mL / min (volume space velocity = 10000 h -1 ).

[0054] Figure 1 This is a sample picture of the monolithic catalyst prepared in Example 1. It can be seen from the picture that the material is evenly coated.

[0055] Figure 2 The results of the activity test of the monolithic catalyst prepared in Example 1 for simultaneous removal of ethane and propane are shown in the figure. It can be seen from the figure that the catalyst prepared in the present invention can effectively achieve the simultaneous removal of ethane and propane, and its effective degradation temperature range is ≥300°C.

[0056] It should be understood that the above detailed description of the technical solution of the present invention with the help of optimized embodiments is illustrative rather than restrictive, and it cannot be determined that the specific implementation methods of the present invention are limited to this. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, modifications to the technical solutions recorded in the embodiments, or equivalent replacement of some of the technical features therein, should be deemed to fall within the scope of patent protection determined by the claims submitted for the present invention.

[0057] The above-mentioned embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a metal composite oxide cordierite monolithic catalyst for removing short-chain hydrocarbons, characterized in that: The preparation is carried out by ball milling coating method, and the specific steps include: (1) placing an active metal source precursor in deionized water, ultrasonically dispersing the precursor, and transferring the precursor to a magnetic stirrer for continuous stirring until the precursor solution is completely dissolved to form a stable precursor solution; the active metal source comprises at least one element selected from the group consisting of Mn, Fe, Ni, Co, Ce, Zn, and Cu; (2) adding an aqueous ammonia solution dropwise to the precursor solution during stirring until precipitation occurs; washing the obtained precipitate with deionized water, drying, rolling and screening, and finally calcining to obtain a transition metal composite oxide; (3) preparing a sol according to a binder and deionized water mass ratio of 1: (0-100), dispersing the transition metal composite oxide into the sol according to a solid sol mass ratio of 0.05-0.4, stirring evenly and grinding into a slurry using a ball mill; (4) adding precious metal Pt or Pd to the slurry and stirring to obtain a coating slurry, wherein the amount of Pt or Pd added is 0 to 1.5 wt % of the transition metal composite oxide; (5) pre-treating the honeycomb ceramic cordierite support by immersing it in an acid, drying it, and calcining it; (6) The pretreated honeycomb ceramic cordierite carrier is immersed in the coating slurry, taken out and purged, and then dried and calcined to obtain a monolithic catalyst coated with a complete catalyst layer.

2. The monolithic catalyst for removing short-chain hydrocarbons in exhaust gas according to claim 1, characterized in that: In step (1), the active metal source is one or more of nickel nitrate, cobalt nitrate, cerium nitrate, zinc nitrate, copper nitrate, manganese nitrate and iron nitrate.

3. The monolithic catalyst for removing short-chain hydrocarbons in exhaust gas according to claim 1, characterized in that: In step (4), the noble metal source is one of palladium nitrate, platinum nitrate and chloroplatinic acid.

4. The monolithic catalyst for removing short-chain hydrocarbons in exhaust gas according to claim 1, characterized in that: In step (2), the concentration of aqueous ammonia used in the coprecipitation method is 25-28 wt %.

5. The monolithic catalyst for removing short-chain hydrocarbons in exhaust gas according to claim 1, characterized in that: In step (2), step (5) and step (6), the drying temperature is 70 to 80° C. and the drying time is 10 to 12 hours.

6. The monolithic catalyst for removing short-chain hydrocarbons in exhaust gas according to claim 1, characterized in that: In step (2), step (5) and step (6), the calcination temperature is 400-600° C. and the calcination time is 3-5 hours.

7. The monolithic catalyst for removing short-chain hydrocarbons in exhaust gas according to claim 1, characterized in that: In step (3), the binder is one of pseudo-boehmite, aluminum dihydrogen phosphate sol, alkaline silica sol and hydroxymethyl cellulose, and the mass ratio of the binder to water in the prepared sol is 1: (0-100).

8. The monolithic catalyst for removing short-chain hydrocarbons in exhaust gas according to claim 1, characterized in that: In step (5), the acid used for cordierite pretreatment is one of oxalic acid, nitric acid and hydrochloric acid, and the mass fraction of the acid is 5 to 10 wt %; the cordierite acid pretreatment time is 8 to 12 h; In step (6), the honeycomb ceramic cordierite is immersed in the slurry for 10 to 30 minutes.

9. A metal composite oxide cordierite monolithic catalyst prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the metal composite oxide cordierite monolithic catalyst according to claim 9 in removing short-chain hydrocarbons in exhaust gas, characterized in that: The removal temperature of multi-component short-chain hydrocarbons is 140-550°C.

Citation Information

Cited By

  • Composite oxygen barrier coating and preparation method thereof

    CN120607247A